login
E.g.f. satisfies A(x) = 1/(1 + A(x) * log(1 - x*A(x)))^2.
3

%I #8 Oct 30 2024 08:04:35

%S 1,2,24,562,19974,958468,58085192,4258862844,366713780800,

%T 36281317505040,4056212559155664,505750435243636944,

%U 69586186789180895904,10473322720889293098624,1711744141030969885684320,301912919501972279345773920,57159241548809543158165770240

%N E.g.f. satisfies A(x) = 1/(1 + A(x) * log(1 - x*A(x)))^2.

%F E.g.f.: B(x)^2, where B(x) is the e.g.f. of A377494.

%F a(n) = 2 * Sum_{k=0..n} (2*n+3*k+1)!/(2*n+2*k+2)! * |Stirling1(n,k)|.

%o (PARI) a(n) = 2*sum(k=0, n, (2*n+3*k+1)!/(2*n+2*k+2)!*abs(stirling(n, k, 1)));

%Y Cf. A367159, A377493.

%Y Cf. A377411, A377494.

%K nonn

%O 0,2

%A _Seiichi Manyama_, Oct 29 2024